Do Dopaminergic Impairments Underlie Physical Inactivity in People with Obesity? - Kravitz, Alexxai V.; O'Neal, Timothy J.; Friend, Danielle M. (Frontiers in Human Neuroscience, 2016)
Obesity is associated with physical inactivity, which exacerbates the negative health consequences of obesity. Despite a wide consensus that people with obesity should exercise more, there are few effective methods for increasing physical activity in people with obesity. This lack is reflected in our limited understanding of the cellular and molecular causes of physical inactivity in obesity. We hypothesize that impairments in dopamine signaling contribute to physical inactivity in people with obesity, as in classic movement disorders such as Parkinson’s disease. Here, we review two lines of evidence supporting this hypothesis: 1) chronic exposure to obesogenic diets has been linked to impairments in dopamine synthesis, release, and receptor function, particularly in the striatum, and 2) striatal dopamine is necessary for the proper control of movement. Identifying the biological determinants of physical inactivity may lead to more effective strategies for increasing physical activity in people with obesity, as well as improve out understanding of why it is difficult for people with obesity to alter their levels of physical activity.